2017
DOI: 10.1007/s11113-017-9437-1
|View full text |Cite
|
Sign up to set email alerts
|

Child Home Care Allowance and the Transition to Second- and Third-Order Births in Finland

Abstract: Using register data from the Finnish Census Panel, this paper studies the relationship between the use of the child home care allowance and second and third births among women aged 20–44 in Finland during the period 1992–2007. Discrete-time event-history analysis is applied to examine (i) whether women taking up the child home care allowance while their previous child was under the age of 3 have a higher risk to proceed to subsequent childbearing, (ii) whether these women proceed to a further birth more quickl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Some of these temporal changes are inevitable, but family-friendly policies may have the potential to compensate the negative impact of demographic changes on fertility rates 33 34. Although generous family policies have probably prevented Finland to be one of the countries with the lowest-low fertility with a total fertility rate below 1.3,35 there may still be room for improvement. Awareness of family policies that encourage both fatherhood and motherhood at earlier ages, support young couples and influence spacing between first and second and higher order births, might increase fertility rates.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these temporal changes are inevitable, but family-friendly policies may have the potential to compensate the negative impact of demographic changes on fertility rates 33 34. Although generous family policies have probably prevented Finland to be one of the countries with the lowest-low fertility with a total fertility rate below 1.3,35 there may still be room for improvement. Awareness of family policies that encourage both fatherhood and motherhood at earlier ages, support young couples and influence spacing between first and second and higher order births, might increase fertility rates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationship between gender equality and fertility in the Nordic countries is far from straightforward, as the availability of long parental leaves may help to preserve gender inequality by discouraging mothers' employment (Rønsen and Sundström 2002). Rates of continued childbearing have been shown to be relatively high among mothers who make extensive use of long family leaves (Duvander, Lappegård, and Andersson 2010;Erlandsson 2017). Similarly, public policies promoting gender equality may benefit different groups of women unequally: while differences in cohort fertility by women's level of education have converged (Jalovaara et al 2018), differences in fertility by women's field of education remain (Hoem, Neyer, and Andersson 2006;Rønsen and Skrede 2010).…”
Section: Gender Equality and Fertility In Nordic Countriesmentioning
confidence: 99%
“…They did not specifically test for the impact of the introduction of HCA, but their results indicate that the shortening of birth intervals happened mainly before the introduction of HCA. On the other hand, Erlandsson (2017) found that mothers using HCA with their first or second child are more likely to receive a subsequent child faster than those not using HCA. However, the analysis can not be interpreted as causal, since the results most likely reflect selection of family preferences among mothers.…”
Section: Identification Of Causal Effectsmentioning
confidence: 91%